New species of Bairdioidea (Crustacea, Ostracoda) from the Southern Ocean anddiscussions on Bairdoppilata simplex (Brady, 1880), ?Bairdoppilata labiata(Müller, 1908) and Bythopussella aculeata (Müller, 1908) - Brandão, Simone N. (Zootaxa, 2008)
Only a few bairdioid species were reported from the high Antarctic region of the Southern Ocean. One of these species is the supposedly widely distributed Bairdoppilata simplex (Brady, 1880). The re-study of material previously identified as Bairdoppilata simplex (Brady, 1880) indicates that these specimens should be assigned to several different species. On the basis of the specimens studied herein and of published illustrations it is possible to conclude that more than ten species are represented in the material that has been misidentified under this name, seven of these species were re-studied and are illustrated herein. One of them, Bairdoppilata labiata (Müller, 1908), previously considered a junior synonym of B. simplex, is herein considered a valid taxon and its lectotype is designated. Additionally, in the present publication 82 bairdioid live specimens and 585 valves collected from depths of 1123 to 4932m during the ANDEEP Project in the Atlantic Sector of the Southern Ocean were studied. Seven new species are described—?Neonesidea keyseri sp. nov., Bythocypris praerenis sp. nov., Bythocypris malyutinae sp. nov., Bythocypris polarsterni sp. nov., Bythocypris richarddinglei sp. nov., Bythocypris weddellensis sp. nov., Bythopussella brandtae sp. nov. A new combination is suggested to the bathyal species Bythopussella microguttata (Whatley et al., 1998b) n. comb. (previously described in the genus Bairdoppilata). Statistical analyses (MDS, ANOSIM, BEST_BIOENV, and Cluster) show clear relationships among the bairdioid assemblages and the depth and geographical locality where samples were collected.